Patellar Tendon Reconstruction in Total Knee Arthroplasty: A New Technique - Rajgopal, Ashok; Vasdev, Attique; Dahiya, Vivek (The Journal of Knee Surgery, 2015)
Patellar tendon disruption is one of the most dreaded complications following total knee arthroplasty (TKA) impacting both implant function and implant longevity. To overcome the concerns regarding allografts and improve outcomes with augmentation techniques, we describe a technique, which we have successfully used over the past 4 years with good results. Seven patients underwent reconstruction for patellar tendon disruption using our technique from a cohort of eight patients. Extensor lag improved from a mean of 40 degrees to less than 5 degrees postoperatively. Range of motion improved from a mean of 105 degrees to 115 degrees of flexion. There was improvement in Knee Society Functional Score from a preoperative mean of 30 to 75 points. The Knee Society Pain Score, however, did not show much improvement. We believe our technique to be a solution to the difficult problem of patellar tendon ruptures after TKA and we continue to perform this procedure.
Keywords: patellar tendon rupture; quadriceps tendon graft; bone block; semitendinosus